Strategi Pemasaran Ekspor UMKM Furniture Berbasis Branding dan Diferensiasi Produk Kreatif: Analisis pada CV Delta Raya - Suwarni, Evi; Lestari, Baroroh; Wahyu, Ellyn Eka; Kusumasasti, Ika; Muhammad Az Zuhri6, Fahmi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze branding and product differentiation strategies in optimizing the export of creative economy-based furniture SMEs, with a case study on CV Delta Raya. In facing global competition, export-oriented furniture SMEs require marketing strategies that not only enhance competitiveness in international markets but also create unique values that represent the strength of the local creative economy. Strong branding helps build a positive company image in global markets, while product differentiation ensures competitive advantages that appeal to international consumers. This research employed a qualitative method with a case study approach on CV Delta Raya’s export-oriented furniture SMEs. Data were collected through in-depth interviews with the business owner, direct observation of marketing strategies, and document analysis related to branding, promotion, and product design. The findings indicate that CV Delta Raya has utilized creative economy-based branding through environmentally friendly product positioning, vintage designs with artistic value, and the use of the Timber Legality Verification System (SVLK) as an element of trust in international markets. Product differentiation strategies were implemented by emphasizing production quality, alignment with global design trends, and product customization according to buyer requirements. However, weaknesses remain in digital promotion and limited penetration into new markets beyond existing buyers. In conclusion, branding and product differentiation strategies based on the creative economy have proven effective in strengthening the global market position of furniture SMEs in Batu. To maximize their potential, digital branding enhancement, international market diversification, and collaboration with government and trade associations are recommended to facilitate global promotion.